Interventional management for chronic pain - Dessy R Em.ril (Jurnal Kedokteran Syiah Kuala, 2009)
Abstract.  Chronic  pain is  a common clinical  condition affecting the quality of life  of the population.  This article aims  to review the interventional   options for chronic  pain based on literature researches.   Multiple searches   using Medline   were carried  out  and additional   searches  were  made using   reference lists  of published papers and book chapters.   The article discussed  procedures ranging from selective nerve root or zygapophyseal   (facet)  joint   block   with   local   anaesthetics     to   irreversible   neurodestruction   with radiofrequency energy or neurolytic   agents and  epidural   injection.   Other techniques   include  intraspinal delivery  of  analgesics.   ·  There  is  evidence  that   these  interventional    procedures    are  valuable    both                                           diagnostically   and therapeutically.   (JKS 2009; 3:139-144)Key words: spinal pain, neurophathicpain, intervention Abstrak.    Nyeri   kronik  adalah  kondisi    yang  sering  dijumpai     ciao   mempengaruhi  kualitas    hidup penderitanya.   Artikel  ini bertujuan untuk rnembahas  secara  umum tentang penatalaksanaan intervensi yang bersifat  minimal invasive   pada  nyeri  kronik  berdasarkan review  terhadap  berbagai   literature.   Dalam makalah ini didiskusikan  tentang berbagai prosedur mulai dari prosedur dasar hingga yang lanjut. Sebagian penelitian membuktikan bahwa tindakan intervensi pada  nyeri kronik memberikan manfaat baik secara terapetik maupun diagnostic.   (JKS 2009; 3: 139-144) Kata kunci: nyerispinal, nyeri neuropatik, tindakan intervensi